Exploring the Interplay of Trait Self‐Control and Ego Depletion: Empirical Evidence for Ironic Effects. Issue 5 (24th January 2013) - Imhoff, Roland; Schmidt, Alexander F.; Gerstenberg, Friederike
Abstract Trait self‐control (TSC) has been conceptualized as a general and abstract ability to exert self‐regulation across multiple domains that has mostly beneficial effects. However, its relationship to situational depletion of self‐regulatory resources has received little attention. We systematically explore the interplay of trait and situational self‐control in two studies (total N = 264). In contrast with a positive view of TSC, the results show greater ego depletion effects for high (vs. low) self‐control abilities across such diverse domains as candy consumption (Study 1), risk‐taking behaviour (Study 2) and achievement motivation (Study 2). It is proposed that these ironic effects are attributable to high‐TSC individuals' less frequent active inhibition of impulses in everyday life and their resulting lack of experience in resisting acute temptations. A third study (N> = 358) corroborated this general reasoning by showing that TSC is indeed associated with less frequent impulse inhibition in daily routines. Our data point to a downside of dispositional self‐control in ego depletion paradigms. Other explanations and potential future avenues for resolving inconsistent findings across the literature are discussed. Copyright © 2013 European Association of Personality Psychology